Brexit negotiations after Article 50 : assessing process, progress and impact - de Ruyter, Alex; Nielsen, Beverley (Bingley, U.K. : Emerald Publishing Limited, 2019)
Brexit Negotiations after Article 50: Assessing Process, Progress and Impact brings together contributors from academia, politics and practice to discuss and debate the progress (or lack of) to date since the Prime Minister, Theresa May, enacted the Article 50 process to leave the EU on 29th March 2017.This collection is split into two key areas of inquiry. The first section explores the process of Brexit and the multifaceted aspects of the Article 50 process, examining the arguments for and against membership of the European Union. The second section develops the arguments within the first section by providing thematic chapters on the likely impact of Brexit on particular sectors of the UK economy, namely: the financial services sector; SMEs and related supply chain issues; and, the automotive sector (as an emblematic sector for UK manufacturing).The book will make a unique contribution to the debate on Brexit as it brings together academics and practitioners from both a 'Remain' and 'Leave' persuasion,including Sir Bernard Jenkin, MP, economist Vicky Pryce and philosopher AC Grayling.
Prelims -- Introduction -- Part I: Brexit: progress, process and issues -- 1. Brexit and the question of the UK constitution -- 2. The UK approach to Brexit -- 3. The UK economy and trade post-Brexit -- 4. The British labour party's attitude towards the EU - a brief history -- 5. Explaining the Brexit vote: a socioeconomic and psychological exploration of the referendum vote -- 6. Custom unions and common markets as economic security fault lines: the garlic case -- Part II: Brexit themes -- 7. The impact of Brexit on the city of London -- 8. Brexit and the potential business impact on English SMEs -- 9. Brexit and the auto industry: understanding the issues for supply chain management -- Conclusion: where do we go from here? -- Index.
Includes index.
Keywords: European Union -- Great Britain; European Union -- Membership; Great Britain -- Foreign relations -- European Union countries; European Union countries -- Foreign relations -- Great Britain; European Union countries -- Politics and government -- 21st century; Political Science -- General; Politics & government